2007
DOI: 10.1017/s0266467407004142
|View full text |Cite
|
Sign up to set email alerts
|

Use of a fragmented landscape by three species of opossum in south-eastern Brazil

Abstract: Spatial patterns presented by the opossums Caluromys philander, Philander frenata and Micoureus demerarae were studied, through radio-tracking, in a landscape composed of eight small (1.3–13.3 ha) forest fragments surrounded by a matrix of open vegetation in south-eastern Brazil. Sixteen individuals were fitted with radio-collar transmitters and monitored for 2–8 mo. Fixes were obtained by the ‘homing-in on the animal’ technique. Numbers of locations of each individual varied from 6 to 117. Home ranges sizes r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 33 publications
3
41
0
8
Order By: Relevance
“…Pitfalls had higher total capture success than Sherman traps placed either on the ground or in trees, confirming similar results found in several habitats in Brazil, which found that pitfalls were three to eight times more efficient (Lyra-Jorge and Pivello, 2001;Hice and Schmidl, 2002;Umetsu et al, 2006). This high efficiency of capture observed for pitfalls may be related to the likelihood of capturing more than one individual in the same trap, which was observed during this study on many occasions.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Pitfalls had higher total capture success than Sherman traps placed either on the ground or in trees, confirming similar results found in several habitats in Brazil, which found that pitfalls were three to eight times more efficient (Lyra-Jorge and Pivello, 2001;Hice and Schmidl, 2002;Umetsu et al, 2006). This high efficiency of capture observed for pitfalls may be related to the likelihood of capturing more than one individual in the same trap, which was observed during this study on many occasions.…”
Section: Discussionsupporting
confidence: 89%
“…Pitfalls were more efficient in the fragment A and corridor. These habitats were dominated by rodents, which are generally captured more in pitfalls, as found in other studies (Silva, 2001;Lyra-Jorge and Pivello, 2001;Umetsu et al, 2006). For the corridor, besides the higher capture of rodents, there was also no capture in Sherman tree traps, probably due to its thin canopy.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…After release, food was kept outside the fence until the animals became independent from the supplementation, which happened after 15 days approximately. All reintroduced animals were equipped with radio collars for radiotracking using the modified "homing in on the animal" method (Lira et al, 2007). They were daily or weekly monitored depending on time after release.…”
Section: Field Observation Of Carrion Consumptionmentioning
confidence: 99%
“…The Brazilian Common Opossum is widely spread in Brazil -especially in the Atlantic Forest and Restinga -Argentina and Paraguay. Ecologically, it attracted special attention due to its capacity to adapt to different conditions and to persist forest fragmentation in advance of the creations of urban areas [12,13,22,32,38,41].…”
Section: Introductionmentioning
confidence: 99%